Prevalence of, and factors associated with, sarcopenia in Iran: a systematic review and meta-analysis - Marzban Abbas Abadi, Mobin; Hosseinzade, Danial; Khalilizad, Majid (Frontiers in Nutrition, 2025)
BackgroundSeveral studies have assessed the epidemiology of sarcopenia in Iran with conflicting results, but comprehensive information has remained limited. Therefore, we aimed to perform a systematic review and meta-analysis of the prevalence of sarcopenia and its associated factors among Iranian population.MethodsWe searched in Embase, PubMed, Scopus, and Google Scholar, as well as Persian databases including the Scientific Information Database and Magiran, from inception to 31 May 2024. We included cross-sectional observational studies reporting the prevalence rate of, and/or factors associated with, sarcopenia in Iranian population. The pooled prevalence of sarcopenia was estimated using a random-effects model.ResultsTotally, 14 eligible studies were included. The overall pooled prevalence of sarcopenia in Iran was 22.1% (95% confidence interval [CI]: 18.7–25.6). This rate in older adult population (≥60 years) was 23.5% (95% CI: 17.9–29.0). Sarcopenia was more prevalent in men (23.2% [95% CI: 21.3–25.1]) than in women (15.5% [95% CI: 9.2–21.9]). The prevalence of severe sarcopenia was 24.5% (95% CI: 16.9–32.0). Factors associated with an increased risk of sarcopenia included older age, male gender, higher body fat, lower socioeconomic status, lower education, insufficient physical activity, diabetes, smoking, and malnutrition; conversely, dietary patterns rich in anti-inflammatory nutrients, Mediterranean diet adherence, and higher mineral and vitamin intake were associated with a lower likelihood of sarcopenia.ConclusionThe prevalence of sarcopenia is notably high in Iran, particularly among men and older ages. These findings emphasize the need for targeted interventions in nutrition and lifestyle to reduce sarcopenia risk and improve quality of life among Iranians.